Integral mission in seven words - Xavier, Érico Tadeu; Malheiros, Isaac (Kairós: Revista Acadêmica da Prainha, 2021)
The integral mission of the Church is fulfilled as the Church conforms itself to the different dimensions that constitute its life and missionary activity. These dimensions can be summarized in the Greek words found in the New Testament, and analyzed in this article, through an exegetical and bibliographical research, in order to clarify their importance in the contemporary Church. In this article, will be used as a reference the seven Greek words most frequently used in the New Testament to describe the life and missionary activity of the Church. The Church: a) witnesses (μαρτυρέω); b) adores (λειτουργέω); c) shepherds (ποιμαίνω); d) serves (διακονέω); e) shares (κοινωνέω); f) teaches (διδάσκω); g) proclaims (κηρύσσω).